An actionable guide to the United Nations' Biodiversity Beyond National Jurisdiction Agreement for research scientists - Jeffrey Marlow; Arianna Broggiato; Janine Felson; Harriet Harden‐Davies; Rebecca Helm; Marcel Jaspars (Limnology and Oceanography, 2026)
The United Nations' “Biodiversity Beyond National Jurisdiction” (BBNJ) Agreement establishes a broad framework regulating activities—including scientific research—in marine Areas Beyond National Jurisdiction (ABNJ), with the aim of advancing long‐term conservation and sustainable use. Here, we offer a practical guide for researchers hoping to understand how the BBNJ Agreement will impact their work upon entry into force, highlighting relevant requirements , recommendations , and opportunities . Researchers will be required to submit pre‐ and post‐cruise reports to a centralized online repository, as well as information about downstream research and development, including commercialization. Capacity building efforts to bolster the scientific proficiency of developing countries will also be required, though the guidance on precise modalities is broad and allows for customization. The BBNJ Agreement recommends a range of activities around capacity building and technology transfer that individual researchers could initiate, including research exchanges and infrastructure improvement. There are also many opportunities for researchers to support the Agreement's conservation and sustainability objectives through, for example, proposing marine protected areas, conducting environmental impact assessments, or joining technically oriented subsidiary bodies that will add practical detail to the Agreement's implementation in the years to come. Overall, many of the BBNJ Agreement's prescriptions align well with current best practices regarding collaboration, cruise operation, and data sharing. Given the deep integration of science into the BBNJ Agreement, marine scientists aiming to work in ABNJ are poised to both benefit and benefit from the Agreement's forward‐looking objectives.